The Effect Of Motivation, Communication And Work Stress On Employee Satisfaction Pt. Indako Trading Coy Medan - Jason Jonatan; Viona Wijaya; Khomeiny Yunior (Jurnal Mantik, 2022)
Motivation, communication and work stress are elements that can affect employee job satisfaction. This study aims to determine and analyze the effect of motivation, communication and job stress on job satisfaction of employees of PT. Indako Trading Coy Medan. This type of research is explanatory research. The research population that will be used in the study are all employees from each division who work at PT. Indako Trading Coy Medan during the period from January to December 2021 with a total population of 113 employees. Due to the total population of only 113 employees, the sampling technique that will be used is saturated sampling where the sampling is saturated in the research that will be divided into questionnaires measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous test and partial test. The results showed that either partially or simultaneously, motivation, communication and job stress have a positive and significant effect on job satisfaction of PT. Indako Trading Coy Medan. Based on the results of this study, the implications for management are to increase motivation, communication and decrease employee work stress